Increased incidence of traffic accidents in Toxoplasma-infected military drivers and protective effect RhD molecule revealed by a large-scale prospective cohort study - Flegr, Jaroslav; Klose, Jiří; Novotná, Martina; Berenreitterová, Miroslava; Havlíček, Jan (BMC infectious diseases, 2009)
BACKGROUND: Latent toxoplasmosis, protozoan parasitosis with prevalence rates from 20 to 60% in most populations, is known to impair reaction times in infected subjects, which results, for example, in a higher risk of traffic accidents in subjects with this life-long infection. Two recent studies have reported that RhD-positive subjects, especially RhD heterozygotes, are protected against latent toxoplasmosis-induced impairment of reaction times. In the present study we searched for increased incidence of traffic accidents and for protective effect of RhD positivity in 3890 military drivers. METHODS: Male draftees who attended the Central Military Hospital in Prague for regular entrance psychological examinations between 2000 and 2003 were tested for Toxoplasma infection and RhD phenotype at the beginning of their 1 to 1.5-year compulsory military service. Subsequently, the data on Toxoplasma infection and RhD phenotype were matched with those on traffic accidents from military police records and the effects of RhD phenotype and Toxoplasma infection on probability of traffic accident was estimated with logistic regression. RESULTS: We confirmed, using for the first time a prospective cohort study design, increased risk of traffic accidents in Toxoplasma-infected subjects and demonstrated a strong protective effect of RhD positivity against the risk of traffic accidents posed by latent toxoplasmosis. Our results show that RhD-negative subjects with high titers of anti-Toxoplasma antibodies had a probability of a traffic accident of about 16.7%, i.e. a more than six times higher rate than Toxoplasma-free or RhD-positive subjects. CONCLUSION: Our results showed that a common infection by Toxoplasma gondii could have strong impact on the probability of traffic accident in RhD negative subjects. The observed effects could provide not only a clue to the long-standing evolutionary enigma of the origin of RhD polymorphism in humans (the effect of balancing selection), but might also be the missing piece in the puzzle of the physiological function of the RhD molecule.
Keywords: logistické modely; Phenotype; krevní skupiny - systém Rh-Hr; ozbrojené síly; Toxoplasmosis; mladý dospělý; Logistic Models; Accidents, Traffic; lidé; Military Personnel; Risk Factors; Incidence; prospektivní studie; protilátky protozoální; Male; Antibodies, Protozoan; incidence; Prospective Studies; Young Adult; polymorfismus genetický; rizikové faktory; toxoplazmóza; fenotyp; mužské pohlaví; Rh-Hr Blood-Group System; Polymorphism, Genetic; dopravní nehody; Humans